MARKETING ACTION PLANNING AND THE ROLE OF HUMANS IN MUHAMMADIYAH PARTNERS BUILT SMEs MALANG REGION - Thoyib, Armanu; Islam F, Muhammad Fajrul; Suryadi, Nanang (FKIP Universitas Wisnuwardhana, 2023)
MSMEs are born and established naturally, it can be due to the strong intention of the founder to do business independently, the family environment and can also be due to friendships that make MSMEs grow, stand and develop. This service aims to assist MSMEs in accelerating business adjustments following the development of a dynamic business environment and to improve the ability of MSMEs in marketing aspects and creating human resource value. The FEB UB service team approaches MSMEs collaboratively, namely by working with MSME owners to identify the needs and challenges faced in marketing and human resource management. The implementation of this service is by means of training, workshops, consultations, and assistance from the service team. The result is an improvement in the marketing capabilities of MSMEs with the adoption of more effective digital marketing strategies and techniques. MSMEs are able to utilize digital platforms to increase product visibility and reach more potential customers. In addition, MSMEs are expected to optimize human resource management with the implementation of SOPs (Standard Operating Procedures) and improved quality of service to customers. Thus, MSMEs will be able to compete better and improve business competitiveness. MSMEs need to open themselves to learn and adapt to change. MSMEs can take advantage of cooperation and relationships in business organizations to support each other and expand business networks. Strengthening collaboration among entrepreneurs will help MSMEs face challenges together and improve their ability to compete in the market. Finally, MSMEs are advised to keep abreast of technological developments and consumer tastes in order to remain relevant and innovative in running their businesses. Keywords: Planning, Marketing Action, Human Role, Muhammadiyah-assisted MSMEs